2015
DOI: 10.1002/uog.13420
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of lung area measurements by two‐dimensional ultrasound in fetuses with isolated left‐sided congenital diaphragmatic hernia

Abstract: Objective To evaluate lung growth in healthy fetuses and those with congenital diaphragmatic hernia (CDH) using two-dimensional (2D) ultrasound. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In a previous study, Ruano et al attempted to evaluate longitudinal behavior of lung size in a cohort of 52 isolated left‐sided CDH fetuses and 66 healthy fetuses without congenital malformations and found different lung growth patterns between study groups. The CDH group showed a reduced lung growth rate and a progressive deterioration of lung size throughout pregnancy as compared with the control group.…”
Section: Commentmentioning
confidence: 98%
See 3 more Smart Citations
“…In a previous study, Ruano et al attempted to evaluate longitudinal behavior of lung size in a cohort of 52 isolated left‐sided CDH fetuses and 66 healthy fetuses without congenital malformations and found different lung growth patterns between study groups. The CDH group showed a reduced lung growth rate and a progressive deterioration of lung size throughout pregnancy as compared with the control group.…”
Section: Commentmentioning
confidence: 98%
“…Similarly, the proportion of abnormal IPa Doppler parameters at diagnosis and at last examination before delivery was significantly higher in nonsurvivors than survivors ( Figure 5). Logistic regression analysis showed that O/E-LHR, liver position, and intrapulmonary-artery Doppler indices were significantly In a previous study, Ruano et al 19 attempted to evaluate longitudinal behavior of lung size in a cohort of 52 isolated left-sided CDH fetuses and 66 healthy fetuses without congenital malformations and found different lung growth patterns between study groups. The CDH group showed a reduced lung growth rate and a progressive deterioration of lung size throughout pregnancy as compared with the control group.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 2 more Smart Citations
“…Whether this is an independent predictor remains uncertain. Others suggest using serial measurements for prognostication, but this may not be practical . Far less is known about the uncommon right‐sided CDH; however lung size, determined by US or MR, seems to be predictive, but the values for severity of hypoplasia used for left‐sided lesions cannot be interchanged with those used for right‐sided lesions .…”
Section: Fetal Therapymentioning
confidence: 99%